Theme-types and Thematic (Progression) Patterns in the Argumentative Essays by Second-Year English Major Students from the Université André Salifou - ALLAGBE, Ayodele Adebayo; ZOUNHIN TOBOULA, Coffi Martinien; TANKARI, Moussa (My University, 2023)
This paper aims at analyzing the Theme-types and Thematic (progression) patterns in the argumentative essays written by second-year English major students from the Université André Salifou (henceforth, UAS), Niger Republic. Drawing its theoretical underpinnings from Systemic Functional Linguistics (henceforth, SFL) and the descriptive mixed research method, the study randomly selected and examined 10 out of the 80 argumentative essays (i.e., 12.50%) written by the English as Foreign Language (henceforth, EFL) students enrolled in the second year (2020-2021). The findings revealed that 8 out of the 10 texts contain two Theme-types: Topical Themes and Textual Themes. They also showed that most of the Topical Themes are unmarked, suggesting that the subjects in the clauses occur in their usual slots. The marked Themes, though they exist in low proportions in the texts, proved that the texts are rhetorically well-organized. The use of Textual Themes in the texts exuded too that the texts are rhetorically well-organized. Again, the findings indicated that all the texts comprise two major Theme classes (a and b), the dominant type being Theme class (a), confirming once more that Topical Themes are placed in their usual slots. Finally, the findings unveiled that only two types of Thematic progression pattern were selected in the texts: Theme reiteration and the zig-zag pattern. In other words, the multiple-Rheme pattern is absent from the texts, indicating that the students still find it difficult to organize their texts. Hence, more efforts should be devoted to text creation and organization in the EFL writing class.
Keywords: Argumentative essays; Theme-types; textual meaning; thematic pattern; thematic progression pattern